Mixed Learning Post Pandemic Solutions - Prawisanthi, Tasya; Ni Made Ratminingsih (International Journal of Language and Literature, 2023)
The uncertainty caused by the Covid-19 pandemic has impacted many sectors, including the education sector. Students, teachers, and institutions must be able to survive in conditions where distance learning is implemented. Blended Learning (BL) is one of the methods applied internationally during the pandemic. This study aims to investigate the advantages, challenges, and effectiveness of BL. The research method is a systematic literature review (SLR) with a qualitative descriptive research type. This research is a systematic literature review. Researchers explore various literature from various journals accredited by Scopus to Sinta. This study reveals various findings regarding its advantages, challenges, and effectiveness. The main results of this study are to show that this model offers high flexibility and effectiveness in the learning process. This study found that blended learning not only increases the accessibility of education but also encourages higher student engagement through the use of technology and interactive media. In addition, this model allows for personalization of learning, where students can learn according to their own pace and learning style. It also provides opportunities for teachers to develop more innovative and responsive learning strategies to change. This research implies that these findings encourage the development of a more flexible and adaptive curriculum that can optimally combine online and face-to-face learning.